Anti-inflammatory Effect of Ethanol Extract of Belamcandae Chinensis (L.) in Lipopolysaccharide-stimulated RAW264.7 Macrophages by Suppressing NF- κB Activation - Phuong Thanh, Mai; Anh, Pham Thi; Kim Thu, Ninh Thi; Anh Phuong, Pham Do; Hao, Bui Thi; Minh, Phan Hong (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
The medicinal herb Belamcanda chinensis (L.) is utilized in traditional medicine for its diverse effects on inflammatory conditions. Nevertheless, experimental data are scarce regarding the anti-inflammatory properties of extracts derived from various parts of Belamcanda chinensis . This research was conducted to explore the anti-inflammatory effects and possible molecular mechanisms of ethanol extracts from the aerial parts (ML1) and rhizomes (MT1) in lipopolysaccharide-stimulated (LPS) RAW264.7 macrophages. The extracts of Belamcanda chinensis demonstrated a concentration-dependent inhibition of NO production in LPS-stimulated RAW264.7 macrophages. Notably, the MT1 extract exhibited a more pronounced reduction in NO production compared to the ML1 extract. Further investigation of the molecular mechanisms underlying the anti-inflammatory effects revealed that MT1 reduced NF-κB expression, as shown by Western blot analysis. These findings imply that the anti-inflammatory action of the ethanol extract from Belamcanda chinensis is associated with the suppression of NO production via the downregulation of NF-κB activity in LPS-stimulated RAW264.7 macrophages.